Proposal of mutation-based bees algorithm (MBA) to solve traveling salesman & jobs scheduling problems - Chaweshly, Saran Akram (Engineering and Technology Journal, 2010)
هذا البحث يقدم خوارزمية مطورة و معتمدة على التحشد و هي خوارزمية النحل و معامل الطفرة. خوارزمية النحل المعتمدة على الطفرة هي خوارزمية مفيدة جدا لحل بعض مشاكل من نوع NP-complete. هذا البحث يحوي النسخة الأساسية من خوارزمية النحل المعتمدة على الطفرة لحل مشكلتين من نوع NP-complete كإجراء لغرض اختبار الخوارزمية المقترحة. و هاتان المشكلتان هما مشكلة البائع المتجول و مشكلة جدولة الوظائف. نتائج التجارب أثبتت أن النموذج المقترح مناسب جدا لحل مشاكل من نوع NP-complete و قد أعطت نتائج جيدة بالمقارنة مع خوارزمية النحل التقليدية. This paper presents an improved swarm-based algorithm which is based on Bees Algorithm and Mutation Operator. Mutation-based Bees Algorithm (MBA) is very useful to solve some NP-complete problems. This paper contains the basic version of MBA with solving two NP-complete problems as examples and experiments for testing the suggested approach. These two problems are Traveling Salesman Problem and Job Scheduling Problem. The experimental results show that the suggested approach is very suitable for solving NP-complete problems and gives good results compare with traditional Bees algorithm.